Synthesis of chitosan based magnetic molecularly imprinted polymers for selective separation and spectrophotometric determination of histamine in tuna fish. (1st December 2017) - Hashemi, Mahdi; Nazari, Zahra; Noshirvani, Nooshin
Highlights: Magnetic chitosan based MIPs were used for SPE of His. Adsorption capacity of MIPs was improved using chitosan as a functional monomer. Adsorption kinetic and adsorption isotherms were investigated. His was preconcentrated on this sorbent and determined spectrophotometrically. Abstract: A novel chitosan molecularly imprinted polymers (CHI/MIPs) coated on Fe3 O4 magnetic nanoparticles (MNPs) for selective solid phase extraction (SPE) of histamine (His) was synthesized by cross-linking of CHI with (3-Glycidyloxypropyl) trimethoxysilane (GPTMS) in the presence of His as the template molecule, and GPTMS/MNPS. Synthesized sorbent was characterized by scanning electron microscopy, X-ray diffraction, FT-IR and via adsorption kinetics and adsorption isotherms. The application of this sorbent was investigated in preconcentration and spectrophotometric determination of His by charge transfer complexation. The method is based on the adsorption of His on CHI/MMIPs and subsequent reaction of desorbed His with 2, 3-Dichloro 5, 6-dicyano- p -benzoquinone (DDQ) reagent for final spectrophotometric detection. The experimental parameters affecting separation efficiency and spectrophotometric determination were optimized. Under optimum conditions and at an analytical wavelength of 468 nm, the calibration plot is linear in the 5.0–160.0 ng mL −1 concentration range, and the limit of detection (estimated at S/N = 3) is 1.5 ng mL −1 . The intra-day and inter-day precisions are in the range from 2.9 to 4.1%. The method was successfully applied for determination of His in spiked tuna fish samples where it gave recoveries ranging from 94.3 to 107.0%.